Influence of small forms of active rest on intellection of students of agrarian higher institutes. - Prysjazhnuk S.I (Kharkov National Pedagogical University, 2012)
Influence of facilities of active rest is considered on the increase of mental capacity of students. In research took part 105 students with the low level of physical preparedness. Progress of students is select the integral index of mental capacity. It is set that the most effective factors of diminishing of action of processes of fatigue and increase of mental capacity of students is the use of small forms of active rest during an educational day. It is suggested to utillize athletic pauses (minutes, micro pauses) during the leadthrough of employments on theoretical disciplines. It is set that small forms of active rest in combination with a leadthrough independent health-improvement-trainings employments on physical self-perfection instrumental in the substantial improvement of the state of physical and mental capacity of student young people.